Knowledge, Attitudes, and Perceptions towards Hand Hygiene Practice Amongst Students at a Nursing College in Lesotho - Malehlohonolo Ntaote; Londele Tyeshani; Olanrewaju Oladimeji (Hygiene)
Background: Hands are critical vectors for microorganisms that cause healthcare-associated infections (HAIs). Hand hygiene, being done the right way, at the right time, and being given the right priority in a healthcare setting is an effective strategy to reduce HAIs and associated costs. Different strategies have been put in place to help improve hand hygiene compliance among healthcare workers; amongst them, continuous training is advised at all levels of care. Aim: This study, focusing on nursing students, aimed to describe their knowledge, attitudes, and perceptions towards hand hygiene, highlighting their crucial role in maintaining health and preventing infections. Methods: This study was a quantitative cross-sectional study. One hundred and fourteen questionnaires were distributed; 103 were filled out and returned by willing students at Maluti Adventist College, thus a 90% response rate. Results: 62% (64) demonstrated moderate knowledge, all had positive attitudes, and 61% (63) had a positive perception towards hand hygiene. There was a significant (p-value = 0.012) association between knowledge and training. Conclusions and recommendations: These provide valuable input for enhancing the World Health Organization’s (WHO) hand hygiene multimodal strategy, the SAFE LIFE Clean YOUR HAND campaign, and healthcare workers’ teaching curriculum. All stakeholders should implement strategies that prioritize knowledge dissemination to promote effective hand hygiene practices among healthcare workers worldwide.